Load rating of bridge-size reinforced concrete arch culverts. Issue 3 (4th March 2022) - Jawdhari, Akram; Peiris, Abheetha; Harik, Issam
Abstract: Of the 604, 485 bridges in the United States, approximately 21% are culverts having a span of 6 m (20 ft) or greater. The load rating of typical bridges presents numerous challenges. Developing load ratings for non-typical structures, such as buried arch-shaped culverts is more complex because of the culverts' unique geometric configuration and their interaction with soil media. This paper proposes an alternative analytical method for load rating in-service reinforced concrete (RC) arch culverts that overcomes the limitations of the widely used elastic frame concept while being straightforward to implement. The proposed analytical method uses two-dimensional finite element models of the arch structure and surrounding soil media. The finite element model was first validated against experimental tests on a full-scale RC arch culvert, subjected to simulated live loads. The validated FE model was used in load rating analysis of 21 RC arch culverts with large fills. It was found that for arch culverts with fills exceeding 2.43 m (8 ft.), the controlling actions are bending moments at the crown and haunch. For culverts with fills greater than 3.05 m (10 ft.), live load effects become negligible. A revised rating formula is proposed for culverts with this characteristic.